POLA INTERAKSI DALAM ALQURAN YANG TERCERMIN PADA AYAT-AYAT BERBENTUK PERTANYAAN - Moh. Ainin; Imam Asrori (Fakultas Sastra Universitas Negeri Malang, 2012)
The Qur’an is a media of interaction between God and His creatures. The research aims to describe the pattern of interactions in Qur’an. It uses qualitative design and content analysis. The research result shows that the themes of interaction are various, the participants of interaction include God and His creatures, the responses of the interaction are categorized into: response which is based on its origin and based on the relationship of questions-responses. The motives of interactions are various depending on context. The background of interaction is divided into physical and non-physical. In addition, the pattern of interaction includes one-way and two-way interaction and the interactional strategy is either direct or indirect